Dramatic response to local radiotherapy in a refractory metastatic mediastinal yolk sac tumor patient harboring a germline BRCA2 frameshift mutation: a case report - Xi Cheng; Haiming Yu; Jinying Li; Xiaona Han; Erhong Meng; Houqing Zhou; Dongliang Wang; Beifang Niu; Xiaotao Zhang (Cancer Biology & Therapy, 2022)
Mediastinal yolk sac tumors (YSTs) are highly aggressive germ cell tumors with an extremely poor prognosis. Radiotherapy plays an important role in the treatment of mediastinal YSTs. To maximize benefit from radiotherapy in patients with mediastinal YSTs, exploring functionally relevant biomarkers is essential. Previous studies have demonstrated that mutations in DNA-damage repair (DDR) genes, including BRCA1/2, potentially enhance sensitivity to radiotherapy in solid tumors. However, DDR-gene mutations, as possible predictive biomarkers for radiotherapy in primary mediastinal YSTs, have not yet been reported. Herein, we report a 29-year-old male patient with a refractory metastatic primary YST involving a germline frameshift mutation in the BRCA2 gene (NM_000059.3: exon11: c.4563_4564delAT: L1522fs). During treatment alternation, the patient was found to respond poorly to chemotherapy with or without an immune checkpoint inhibitor but well to radiotherapy. Finally, the patient achieved approximately 17 months of overall survival. To the best of our knowledge, this case report is the first to describe a remarkable response to local radiotherapy in a patient with a refractory metastatic mediastinal YST involving a DDR-gene mutation (germline BRCA2 frameshift variation). This case report provides insightful clues for precision radiotherapy in clinical practice.